Skeletal and dental abnormalities in patients with sex chromosome aberrations: a systematic case-based review - Gruszczyński, Dawid; Nijakowski, Kacper; Wolska-Bułach, Anna; Lacka, Katarzyna (Pediatria Polska - Polish Journal of Paediatrics, 2022)
Sex chromosome aneuploidies (SCAs) are common chromosomal disorders characterised by an atypical number of sex chromosomes. Turner syndrome (TS), Klinefelter syndrome (KS), and Jacobs syndrome (JS) are associated with a wide spectrum of skeletal manifestations, including craniofacial and limb anomalies. This systematic review aimed to analyse the incidence of skeletal abnormalities in selected SCAs based on case reports. In this review, 55 articles were included from the MEDLINE/PubMed and Google Scholar databases, according to PRISMA guidelines. High-arched palate, skeletal class II, and cubitus valgus were most frequently demonstrated among TS patients. Patients with KS and JS most often presented micrognathia, hypertelorism, and flat nasal bridge in the craniofacial region. In contrast, radioulnar synostosis, clinodactyly, and pes planus could be observed in the limbs of KS patients. The presence of dysmorphic facial features and limb malformations may indicate SCAs, which are underdiagnosed in the general population due to a variety of phenotypes.